Utilization Of Household Organic Waste As An Eco-Enzyme For The Growth And Product Of Cultivate Culture (Lactuca sativa L.) - Ronny Nangoi; Rena Paputungan; Tommy B. Ogie; Rafli I. Kawulusan; Rinny Mamarimbing; Frangky J. Paat (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the effect of appropriate Eco Enzyme application on the growth and yield of lettuce (Lactuca sativa L). This study used a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments, namely PO-control, P1 = 15 ml (1.5%) Eco Enzyme / 1 L water, P2 -30 ml (3 %) Eco Enzyme / 1 L water , P4 = 45 ml (4.5%) Eco Enzyme / 1 L water. And each treatment was repeated 4 times to obtain 16 polybags of experimental units. Observational data were analyzed using ANOVA, and if there is a significant difference then a Least Significant Difference (LSD) level of 5% is further tested. The results showed that the administration of various concentrations of Eco Enzyme on the growth and yield of lettuce plants had a significant effect on plant height, number of leaves, and fresh weight, with the best concentration being 4.5% (45 ml) Eco Enzyme / 1 L of water Keywords: Household Organic Waste, Ecoenzyme, Lactuca Growth. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh pemberian Eco Enzyme yang sesuai terhadap pertumbuhan dan hasil tanaman selada (Lactuca sativa L). Penelitian ini Menggunakan Rancangan Acak Lengkap (RAL) non faktorial yang terdiri dari 4 perlakuan taitu P0=kontrol, P1 = 15 ml (1,5 %) Eco Enzyme /1 L air, P2 = 30 ml (3 %) Eco Enzyme /1 L air, P4 = 45 ml (4,5%) Eco Enzyme / 1 L air. Dan setiap perlakuan di ulang sebanyak 4 kali sehingga diperoleh 16 polibag satuan percobaan. Data hasil pengamatan dianalisi mengunakan Anova, dan dan jika terdapat perbedaan yang nyata maka dilakukan uji lanjut Beda Nyata Terkecil (BNT) taraf 5%. Hasil penelitian menunjukkan bahwa pemberian berbagai kosentarsi Eco Enzyme terhadap pertumbuhan dan hasil tanaman selada berpengaruh nyata terhadap tinggi tanaman, jumlah daun, dan bobot segar, dengan kosetrasi terbaik yaitu 4,5% (45 ml) Eco Enzyme / 1 L air. Kata Kunci: Sampah Organik Rumah Tangga, Ecoenzyme, Pertumbuhan Lactuca.